Kristeva and the Political - Sjoholm, Cecilia (Thinking the Political, 2005)
Julia Kristeva is one of the most influential French thinkers of the twentieth century and is best known for her work in linguistics. Even though her work has been very influential, the political implications of her writings have so far been neglected. Kristeva and the Political is the first book to explore the relation of Kristeva's work to the political and casts new light on her work, connecting her to recent developments in literary theory, political theory, and cultural studies. In particular it shows how Kristeva's account of the unconscious and psychoanalysis generally, widens the notion of the political. Each chapter introduces a fundamental theme in Kristeva's work, highlighting a specific period of development in her thought and drawing on texts from the 1960s through to the 1990s. Themes addressed include Kristeva's theory of discourse, the theory of the subject, the notion of alterity, feminism and marginality and her theory known as the 'politics of meaning'. Kristeva and the Political also shows how Kristeva's notions of the political draw on a rich array of thinkers and writers, from Freud, Melanie Klein and Lacan, to Proust and Marguerite Duras.